2013
DOI: 10.4049/jimmunol.1202673
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase Reprograms Lung Tissue and Potentiates Lipopolysaccharide-Induced Acute Lung Injury in Mice

Abstract: We previously reported that removal of sialyl residues primed PBMCs to respond to bacterial LPS stimulation in vitro. Therefore, we speculated that prior desialylation can sensitize the host to generate an enhanced inflammatory response upon exposure to a TLR ligand, such as LPS, in a murine model of acute lung injury. Intratracheal instillation of neuraminidase (NA) 30 min prior to intratracheal administration of LPS increased PMNs in the bronchoalveolar lavage fluid (BALF) and the wet-to-dry lung weight rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…Several groups have reported that removal of surface sialic acids with bacterial sialidases enhanced the response of DCs to LPS. In addition to enhanced maturation and cytokine production upon LPS stimulation, DCs treated with sialidase were also more potent T‐cell activators 8 , 9 , 10 , 11 , 12 , 13 , 14 . These data evidence that sialic acids limit the response of DCs to stimulation via the TLR pathway.…”
Section: Introductionmentioning
confidence: 78%
“…Several groups have reported that removal of surface sialic acids with bacterial sialidases enhanced the response of DCs to LPS. In addition to enhanced maturation and cytokine production upon LPS stimulation, DCs treated with sialidase were also more potent T‐cell activators 8 , 9 , 10 , 11 , 12 , 13 , 14 . These data evidence that sialic acids limit the response of DCs to stimulation via the TLR pathway.…”
Section: Introductionmentioning
confidence: 78%
“…Lung tissue was then air dried for 5-6 days and re-weighed everyday until a dry weight was stable and this acted as the final dry weight. The W/D weight ratio was calculated by dividing the wet by the final dry weight 59 .…”
Section: Methodsmentioning
confidence: 99%
“…The dissected tissues, pallial fluid cell pellet, and hemocytes freshly isolated as described above were lysed by sonication in PBS containing protease inhibitors cocktail (Calbiochem), and the clear supernatant was collected after centrifugation at 3000 rpm for 10 min at 4 °C. For isolation of total RNA the freshly isolated hemocytes, pallial fluid cell pellet, and the aforementioned tissues were extracted by using TRIzole reagent (Invitrogen) as previously described (36). RNA was quantified in a Nanodrop Bioanalyzer at 260/280 nm.…”
Section: Methodsmentioning
confidence: 99%